Superparamagnetic hematite spheroids synthesis, characterization, and catalytic activity. (May 2022) - Vinayagam, Ramesh; Patnaik, Yash; Brijesh, P.; Prabhu, Deepa; Quadras, Melisha; Pai, Shraddha; Narasimhan, Manoj Kumar; Kaviyarasu, K.; Varadavenkatesan, Thivaharan; Selvaraj, Raja
Abstract: The leaf extract of Muntingia calabura is being first reported to be used for the synthesis superparamagnetic hematite nanoparticles by following the green-chemistry approach. Field Emission – Scanning Electron Microscopic image revealed the formation of irregular nano spheroids averaging at 48.57 nm in size and characteristic of Fe and O atoms, as revealed by Energy Dispersive X-Ray spectrum. X-ray diffraction analysis results proved the crystallinity of hematite diffraction planes with crystallite sizes averaging at 30.68 nm. The lattice parameter values stayed concordant with the literature. The superparamagnetic nature was attested by the high value of saturation magnetism (2.20 emu/g) with negligible coercivity and retentivity. Fourier Transform Infrared Spectroscopy results affirmed numerous moieties involved in the synthesis of hematite nanoparticles and the existence of signature Fe–O bands. Thermogravimetric analysis studies portrayed the thermal behavior nanoparticles with 28% weight loss and thermal stability was attained after 700 °C. X-ray photoelectron spectroscopy analysis confirmed the valence states of Fe and O in the hematite nanoparticles and ascertained the purity. The mesoscopic structure was revealed by Brunauer–Emmett–Teller studies with considerable surface area (112.50 m 2 /g). The Fenton-like catalysis mediated by the nanoparticle sample was demonstrated by degrading methylene blue dye. The remarkable degradation efficiency of 93.44% was obtained and the kinetics was conformed to a second-order model with a high R 2 value. Therefore, the highly crystalline and mesoporous superparamagnetic hematite spheroids prepared using the leaf extract of M. calabura would find promising applications in various catalysis processes. Graphical abstract: Image 1 Highlights: Hematite nanoparticles were synthesized using Muntingia calabura leaf extract. Spherical aggregates were witnessed in FE-SEM image. A high specific-surface area of 112.50 m 2 /g was observed by BET analysis. The nanoparticles were superparamagnetic with high Ms value (2.20 emu/g). Fenton-like catalytic degradation of methylene blue dye was demonstrated.